The age of FSES: Portrait of an architect in the frame of education - Kiyanenko, Konstantin (project baikal, 2021)
Basing on the analysis of the Federal State Educational Standards (FSES) and the legislative context of their development and approval, the post-reform history of the standardization of architectural education is viewed with the focus on the transformation of a qualification portrait of an architect as a set of the architect’s qualification characteristics. The article traces the evolution of standards of the last decade, the “age of FSES”. The national FSES of the bachelor degree of the “generation 3++” is compared with the UIA international standard of an architect. The author makes a conclusion whether it is practicable for Russia to use international principles and models of educational standards, the standards of architectural professional practice.
Keywords: state educational standards; architectural education; history of development; cross-cultural analysis